Analysis of α-syn and parkin interaction in mediating neuronal death in Drosophila model of Parkinson's disease - Narwal, Sonia; Singh, Amit; Tare, Meghana (Frontiers in Cellular Neuroscience, 2024)
One of the hallmarks of Parkinson's Disease (PD) is aggregation of incorrectly folded α-synuclein (SNCA) protein resulting in selective death of dopaminergic neurons. Another form of PD is characterized by loss-of-function of an E3-ubiquitin ligase, parkin. Mutations in SNCA and parkin result in impaired mitochondrial morphology, causing loss of dopaminergic neurons. Despite extensive research on individual effects of SNCA and parkin, their interactions in dopaminergic neurons remain understudied. Here we employ Drosophila model to study the effect of collective overexpression of SNCA along with downregulation of parkin in the dopaminergic neurons of posterior brain. We found that overexpression of SNCA along with downregulation of parkin causes reduction in number of dopaminergic neuronal clusters in posterior region of adult brain which is manifested as progressive locomotor dysfunction. Overexpression of SNCA and downregulation of parkin collectively results in altered mitochondrial morphology in a cluster specific manner, only in a subset of dopaminergic neurons of the brain. Further, we found that SNCA overexpression causes transcriptional downregulation of parkin. However, this downregulation is not further enhanced upon collective SNCA overexpression and parkin downregulation. This suggests that the interactions of SNCA and parkin may not be additive. Our study thus provides insights into a potential link between α-synuclein and parkin interactions.These interactions result into altered mitochondrial morphology in cluster specific manner for dopaminergic neurons over a period of time thus unravelling the molecular interactions involved in etiology of Parkinson's Disease.